2015
DOI: 10.17221/932/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 14 soil phosphorus extraction methods applied to 50 agricultural soils from Central Europe

Abstract: Phosphorus (P) is a central element to life on Earth. Living organisms are dependent on a persistent supply of P as it is crucially involved in most major metabolic processes, e.g. in energy transfer as adenosine triphosphate (ATP). Likewise, plants rely on P to secure energy production in photosynthesis (Smil 2000, Ruttenberg 2009). Therefore, the fundamental significance of P in agriculture and food production is beyond question.In nature, we can identify several P pools (Smil 2000, Ruttenberg 2009). The lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
85
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 55 publications
5
85
2
3
Order By: Relevance
“…Basic soil properties were analysed according to standard methods, which are described in detail in Wuenscher et al (2015). Table 1 summarizes selected soil properties and demonstrates the diversity of the soils used in this study; more details are presented in Wuenscher et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Basic soil properties were analysed according to standard methods, which are described in detail in Wuenscher et al (2015). Table 1 summarizes selected soil properties and demonstrates the diversity of the soils used in this study; more details are presented in Wuenscher et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Soil P was extracted with 14 different extraction methods that utilize various mechanisms of extraction and, hence, target different soil P pools; a brief summary of the 14 applied methods is given in Table 2, for more details see Wuenscher et al (2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison studies between different extractants have shown that M-3 can be adapted as a suitable extractant for routine soil analysis (Alva 1993). The Mehlich 3 solution (Wuenscher et al 2015) is an agrochemical extractant used for determination of bioavailable P, Ca, Mg and K for soil fertility assessment in agriculture (with additional potential to determine content of some micronutrients). Extractability of phosphorus is improved by addition of ammonium fluoride and acetic acid.…”
mentioning
confidence: 99%